(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate, in vivo, coronal bacterial infiltration after endodontic treatment with different obturation technique. Forty-five dogs’ root canals, originated from incisors and premolars, were used. The animals were intubated after general anesthesia. After local antisepsis and placement of rubber dam isolation, teeth were opened and instrumented up to a Kerr handfile #40, followed by three obturation protocols with Endofill®: Lateral condensation, Lateral condensation with a coronal plug of set Endofill® and Tagger hybrid technique. Access openings were not sealed and root fillings remained exposed to oral environment for 90 days. After this period, animals were euthanized and specimens were histologically processed and stained with Brown and Brenn. Dentinal tubules were evaluated with presence or absence of bacteria descriptive analysis. Bacterial infiltration was identified on root canal walls in six out of 14 root canals filled with the lateral condensation technique (42,8%), two out of 15 canals filled with Lateral condensation with a plug of set Endofill® (13,3%) and in two out 13 root canals filled with the Tagger hybrid technique (15,3%). Although the use of a coronal plug or a thermomechanical compaction technique showed less bacterial infiltration than conventional lateral condensation, none of the obturation techniques prevented bacterial infiltration to periapical area, evidencing the importance of a proper coronal seal or final restoration.